Service Quality and Customer Repurchase Intention of a Local Restaurant in the Central Philippines - Maria Thely P. Cordova; Nenette D. Padilla (Philippine Social Science Journal, 2025)
To enhance competitive advantage, this descriptive study assessed service quality and repurchase intentions among 157 customers of a local restaurant in a Central Philippine city. Guided by the SERVQUAL model and using validated instruments, the analysis revealed that dine-in customers reported significantly higher satisfaction and loyalty compared to buffet and catering patrons, with key drivers including staff competence, friendliness, and a clean ambiance. While dine-in services successfully fostered trust, the findings highlighted a critical need to improve responsiveness and tangible elements within buffet and catering operations. These insights informed a data-driven service quality plan designed to standardize excellence across all offerings, while future research suggests employing qualitative methods and longitudinal studies to further understand customer motivations and ensure long-term sustainability.